Reduced Ebola vaccine responses in CMV(+) young adults is associated with expansion of CD57(+)KLRG1(+) T cells - Bowyer, Georgina (J Exp Med, 2020)
CMV is associated with immunosenescence and reduced vaccine responses in the elderly (>70 yr). However, the impact of CMV in young adults is less clear. In this study, healthy UK and Senegalese adults aged 18–50 yr (average, 29 yr) were vaccinated with the Ebola vaccine candidate chimpanzee adenovirus type 3–vectored Ebola Zaire vaccine (ChAd3-EBO-Z) and boosted with modified vaccinia Ankara Ebola Zaire–vectored (MVA–EBO-Z) vaccine. CMV carriage was associated with an expansion of phenotypically senescent CD4(+) and CD8(+) T cells expressing CD57 and killer cell lectin-like receptor G1 (KLRG1), which was negatively associated with vaccine responses in both cohorts. Ebola-specific T cell responses induced by vaccination also contained significantly increased frequencies of terminally differentiated CD57(+)KLRG1(+) cells in CMV seropositive (CMV(+)) individuals. This study suggests that CMV can also affect vaccine responses in younger adults and may have a particularly marked impact in many developing countries where CMV seroprevalence is almost universal.